EFFECT OF MOISTURE CONTENT ON SOME PHYSICAL , MECHANICAL PROPERTIES OF LIMA BEAN ( PHASEOLUS LUNATUS ), AN UNDERUTILIZED COMMON FOOD LEGUME - M, Marimuthu; M, Venkatesh; M, Poongodi (Innovare Journal of Agricultural Sciences, 2013)
The physical and mechanical properties of lima bean seeds were determined as a function of moisture content in the range between 11.02 and 0.05 to 24.15± 0.12 . The physical and mechanical properties of lima bean seeds were determined as a function of moisture content in the range of 11.02 ± 0.05 to 24.15± 0.12 d.b.The length, width and breadth of the lima bean seeds increased from 15.32 ± 0.72 to16.16 ± 0.31 mm, 7.92 ± 0.27 to 9.02 ± 0.10 mm, 4.94 ± 0.24 to 5.68 ± 0.26 mm, respectively, with increase in moisture content from 11.02 ± 0.05 to 24.15± 0.12 d.b.One thousand seed weight increased linearly from 423 ± 0.24 to 532 ± 0.32 g. The bulk density decreased from 0.662 ± 0.03 to 0.583 ± 0.13 gcm, while the true density increased from 0.918 ± 0.03 to 1.153 ± 0.13 gcm-3 in the moisture content range. The porosity and sphericity values of lima bean seed increased linearly from 27.88 ± 0.05 to 49.43 ± 1.12, 0.548 ± 0.01 to 0.579 ± 0.09 . The maximum static coefficients of friction were noticed on rubber surface, followed by stainless steel, plywood, galvanized iron, aluminium and glass surfaces. The results are necessary for design of equipment to handling, transportation, processing, and the storage of lima bean seed. Keywords: Lima bean, physical and mechanical properties, moisture content, coefficient of friction, thousand seed mass.